Synovial fluid is a site of citrullination of autoantigens in inflammatory arthritis. - Kinloch, A; Lundberg, K; Wait, R; Wegner, N; Lim, N; Zendman, A; Saxne, T; Malmström, V; Venables, P (2008)
OBJECTIVE: To examine synovial fluid as a site for generating citrullinated antigens, including the candidate autoantigen citrullinated alpha-enolase, in rheumatoid arthritis (RA). METHODS: Synovial fluid was obtained from 20 patients with RA, 20 patients with spondylarthritides (SpA), and 20 patients with osteoarthritis (OA). Samples were resolved using sodium dodecyl sulfate-polyacrylamide gel electrophoresis, followed by staining with Coomassie blue and immunoblotting for citrullinated proteins, alpha-enolase, and the deiminating enzymes peptidylarginine deiminase type 2 (PAD-2) and PAD-4. Proteins from an RA synovial fluid sample were separated by 2-dimensional electrophoresis, and each protein was identified by immunoblotting and mass spectrometry. Antibodies to citrullinated alpha-enolase peptide 1 (CEP-1) and cyclic citrullinated peptide 2 were measured by enzyme-linked immunosorbent assay. RESULTS: Citrullinated polypeptides were detected in the synovial fluid from patients with RA and patients with SpA, but not in OA samples. Alpha-enolase was detected in all of the samples, with mean levels of 6.4 ng/microl in RA samples, 4.3 ng/microl in SpA samples, and <0.9 ng/microl in OA samples. Two-dimensional electrophoresis provided evidence that the alpha-enolase was citrullinated in RA synovial fluid. The citrullinating enzyme PAD-4 was detected in samples from all 3 disease groups. PAD-2 was detected in 18 of the RA samples, in 16 of the SpA samples, and in none of the OA samples. Antibodies to CEP-1 were found in 12 of the RA samples (60%), in none of the SpA samples, and in 1 OA sample. CONCLUSION: These results highlight the importance of synovial fluid for the expression of citrullinated autoantigens in inflammatory arthritis. Whereas the expression of citrullinated proteins is a product of inflammation, the antibody response remains specific for RA.